New methodology for indexing and extracting images - Ismail, Anis; Khawandi, Shadi; Abdallah, Firas (International Journal of Engineering and Technology, 2019)
Indexing and image retrieval has become an interesting area of research today because of the lack of advanced methodologies for indexing and extracting images and the existence of huge amounts of images available everywhere; especially on the web. The available solutions are able to find similar items having the exact shape but not the same item if it has a different shape. In this paper, a new method has been proposed for indexing and extracting images from a database or a folder of images. This database consists of a table of images which contains the paths of the images then we begin the comparison between these images, from this comparison the program displays the percentage of the differences between the images and whether the images are the same or not. The proposed methodology is clever in the way the recovery of images leads to a comparison between images from the pixel. In addition to this, the proposed solution will be able to recognize whether two images having the same shape or not.Â Â Â Â